(untitled) (Journal of Computational Mathematics, 2000)
In this paper, we discuss a posteriori error estimates of the eigenvalue λ_h given by Adini nonconforming finite element. We give an asymptotically exact error estimator of the λ_h. We prove that the order of convergence of the λ_h is just 2 and the λ_h converge from below for sufficiently small h.